Introduction Into the Novel Two-Dimensional Discrete Orthogonal Transforms Based on Rotation Angles - Misans, P.; Derums, U. (Elektronika ir Elektrotechnika, 2011)
A brief description of the novel two dimensional discrete orthogonal transform based on rotation angles is presented. A unified approach for the definition of novel classes of orthogonal transforms is developed. The fast algorithms for the presented transforms are given. Five different subclasses of transforms are provided. A comparison of the number of operations for the calculation of transforms is given. Some examples of sets of basis functions are presented. An initial version of a tool for image analysis and synthesis and generation of basis functions is developed. Ill. 5, bibl. 12, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.112.6.456